2014
DOI: 10.1016/j.apsusc.2013.12.095
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of NOx sensing on WO3 surface: First principle calculations

Abstract: Computational study of NO 2 sensing on the WO 3 (001) surface is presented. Our ab initio calculations reveal a two-step process of NO 2 detection on the WO 3 surface. In a first step the NO 2 molecule is dissociated at an oxygen vacancy site, but a NO molecule remains adsorbed. In a second step NO is re-oxidized into NO 2 by O 2 of the surrounding air leading to the resistance increase which is experimentally observed. We also calculate the adsorption energy of NO on stoichiometric and non-stoichiometric WO 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…For instance, Oison et al [9] clarified that the detection mechanism of O 3 and CO molecules on oxygen deficient WO 3 surface lied in the change of oxygen vacancy concentration and conductivity during the oxidation of CO and the reduction of O 3 . Recently, L. Saadi et al [2] suggested a two-step process for NO 2 detection on WO 3 surface, involving the dissociating and filling of NO 2 molecule on the oxygen vacancy. This study further exhibited the positive role of oxygen vacancy in detection of gases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Oison et al [9] clarified that the detection mechanism of O 3 and CO molecules on oxygen deficient WO 3 surface lied in the change of oxygen vacancy concentration and conductivity during the oxidation of CO and the reduction of O 3 . Recently, L. Saadi et al [2] suggested a two-step process for NO 2 detection on WO 3 surface, involving the dissociating and filling of NO 2 molecule on the oxygen vacancy. This study further exhibited the positive role of oxygen vacancy in detection of gases.…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten trioxide (WO 3 ), which is a wide band-gap n-type semiconductor [1], has been experimentally proved to be a promising gas-sensing material for sensitive detection of various toxic and dangerous gases, such as NO x [2,3], NH 3 [3,4] and CO [3,5,6] and so on. So far, considerable progress has been made in the experimental studies about preparation and gas-sensing properties of WO 3 , especially one-dimensional (1D) nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…In particular we have studied WO 3 , n-type semiconductor to detect O 3 , NO x and CO [8,9]. In the continuity of these works we first have been interested in CuO p-type semiconductor as layer for O 3 detection [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many of previous studies on WO 3 -based sensors were focused on the detection of NO, NO 2 , H 2 , H 2 S and NH 3 [13][14][15], and only a few studies have investigated the gas-sensing performance toward volatile organic compounds (VOCs), such as n-butanol, methanol, ethanol and acetone [16]. VOCs are numerous, varied, ubiquitous and some of them are dangerous to human health or cause harm to the environment [17].…”
Section: Introductionmentioning
confidence: 99%